Safety and Efficacy of Glucomannan for Weight Loss in Overweight and Moderately Obese Adults - Joyce K. Keithley; Barbara Swanson; Susan L. Mikolaitis; Mark DeMeo; Janice M. Zeller; Lou Fogg; Jehan Adamji (Hindawi Limited, 2013)
Background. Few safe and effective dietary supplements are available to promote weight loss. We evaluated the safety and efficacy of glucomannan, a water-soluble fiber supplement, for achieving weight loss in overweight and moderately obese individuals consuming self-selected diets. Methods. Participants were randomly assigned to take 1.33 grams of glucomannan or identically looking placebo capsules with 236.6 mL (8 ounces) of water one hour before breakfast, lunch, and dinner for 8 weeks. The primary efficacy outcome was change in body weight after 8 weeks. Other efficacy outcomes were changes in body composition, hunger/fullness, and lipid and glucose concentrations. Safety outcomes included gastrointestinal symptoms/tolerance and serum liver enzymes and creatinine levels. Results. A total of 53 participants (18-65 years of age; BMI 25-35 kg/m2) were enrolled and randomized. The two groups did not differ with respect to baseline characteristics and compliance with the study supplement. At 8 weeks, there was no significant difference between the glucomannan and placebo groups in amount of weight loss (−.40±.06 and −.43±.07, resp.) or other efficacy outcomes or in any of the safety outcomes. Conclusions. Glucomannan supplements administered over 8 weeks were well tolerated but did not promote weight loss or significantly alter body composition, hunger/fullness, or lipid and glucose parameters. This trial is registered with NCT00613600.